2005
DOI: 10.1111/j.1744-7909.2005.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Escherichia coli of Three Different Soybean Late Embryogenesis Abundant (LEA) Genes to Investigate Enhanced Stress Tolerance

Abstract: In order to identify the function of late embryogenesis abundant (LEA) genes, in vitro functional analyses were performed using an Escherichia coli heterologous expression system. Three soybean late embryogenesis abundant (LEA) genes, PM11 (GenBank accession No. AF004805; group 1), PM30 (AF117884; group 3), and ZLDE-2 (AY351918; group 2), were cloned and expressed in a pET-28a system. The gene products were separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and identified by mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 20 publications
1
22
1
Order By: Relevance
“…A similar conclusion can be reached for the ability of AfLEA1.3 to ameliorate the impact of salt stress on mitochondrial function in Figure 5. Protection against salt and osmotic stress by transgenic expression of plant LEA proteins has also been demonstrated in yeast and bacteria (Lan et al, 2005;Yu, 2005). Furthermore, the glucose starvation-inducible protein B (GsiB; Bacillus subtilis) shows high similarities with group 1 LEA proteins (Stacy and Aalen, 1998) and GsiB domain carrying proteins are involved in high-salt tolerant Escherichia coli strains (Kapardar et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…A similar conclusion can be reached for the ability of AfLEA1.3 to ameliorate the impact of salt stress on mitochondrial function in Figure 5. Protection against salt and osmotic stress by transgenic expression of plant LEA proteins has also been demonstrated in yeast and bacteria (Lan et al, 2005;Yu, 2005). Furthermore, the glucose starvation-inducible protein B (GsiB; Bacillus subtilis) shows high similarities with group 1 LEA proteins (Stacy and Aalen, 1998) and GsiB domain carrying proteins are involved in high-salt tolerant Escherichia coli strains (Kapardar et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…E. coli expressing a modified recombinant PM2 with a duplicated 22-mer repeat region (a variant of the 11-mer motif typical of group 3 proteins) exhibited higher salt tolerance levels than bacteria containing proteins with a single repeat region, implicating the repeat region as the functional domain of the LEA protein. This approach was extended to analyse the protective effect of soybean LEA proteins from all three major groups: group 1 (PM11; Em homologue) and group 3 (PM30) proteins offered protection against both salt stress and cold stress, but the group 2 protein, ZLDE-2, was ineffective (Lan et al 2005). Intriguingly, Campos et al (2006) have presented evidence suggesting that certain LEA proteins are growth inhibitory in E. coli.…”
Section: Transgenic Studiesmentioning
confidence: 99%
“…Guo et al 21 observed the drought tolerance in E.coli cells transformed with the ThPOD3 from Tamarix hispida. LEA proteins from soybean improved tolerance to E. coli cells against salt stress 22 . In order to examine the function of proteins against diverse abiotic stresses, recombinant plasmid was expressed in E. coli.…”
Section: Discussionmentioning
confidence: 99%